(3GdGSJTQGb GdQhSj hGdYGde GdESdGej (B:s (3ef JGQjN GdGSJTQGb hOQGSGJ GdGSJYQGH GdYdej aj QhSjG (B/s - (3GdMeRI, eMehO Mehs 1954- ((3GdOhMI (B- (3bWQ (B:s (3eDSSI hYj ddOQGSGJ hGdCHMGK,s, 2022)
(3hVM GdcJGH HCf eOQSI GdGSJTQGb GdGSJYQGH aj QhSjG JJeJY HJGQjN YQjb hSeYI YdejI bjeI, dCfgG GfUaJ GdYdhe GdYQHjI hbjeJgG HehVhYjI hMjGO Ydej(B. (3dPdc cQS gPG GdcJGH ddMOjK Yf JGQjN GdGSJTQGb GdQhSj Ydi eOi CcKQ ef (B300 (3SfI, hYf GdYdGbGJ GdQhMjI Hjf QhSjG hGdeTQb GdYQHj GdESdGej hGdeSjMj NdGd Cda SfI(B. (3hjSdW GdcJGH GdVhA Ydi JGQjN OQGSI GdeNWhWGJ GdYdejI GdYQHjI hOhQ GdeSJTQbjf GdQhS hGSgGeGJge aj EMjGA GdJQGK GdYdej GdYQHj hGdESdGej(B.s
(3HHdjhLQGajI (B: (3UaMI (B451-458.s
Keywords: (3GdGSJTQGb hGdeSJTQbhfs -- (3OaY eWGYfs -- (3QhSjGs -- (3QhSjGs